FORMULATION & EVALUATION OF MELOXICAM SOLID DISPERSION INCORPORATED TOPICAL GELS - M.A.SALEEM; SUMANJI BALA (International Journal of Pharma and Bio Sciences, 2010)
Solid dispersion complexes of meloxicam were prepared by using cyclodextrins (BCD, HPBCD), PVP and urea by kneading method in different molar and weight ratios. The complexes were characterized by DSC and IR, suggested that no chemical interaction between drug and carrier. The solubility, dissolution and permeability was studied for prepared complexes. The solubility, dissolution and permeability of complexes was markedly increased as compared to pure drug. Solid complexes were incorporated in 1% carbopol to prepare gels and evaluated for pH ,drug content, viscosity, invitro permeability through rat skin . Invitro permeation study reveals that the flux (Jss) and enhancement factor increases with increase in concentration of BCD, HPBCD and decreased dramatically in case of HPBCD with ratio of 1:2. Similar changes in pattern of permeation were observed with urea and PVP complexes .Hence it can be concluded that solid dispersion complex incorporated gel shows highest permeation as compared to plain drug gels.